The Role of Family Communication and Peer Groups in Adolescent Sexual Attitudes: A Phenomenological Study on the Friends with Benefits (FWB) Phenomenon in Jakarta - Pabundu, Devina Dhea (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study examines how family communication patterns and peer group dynamics shape adolescents’ and emerging adults’ engagement in Friends with Benefits (FWB) relationships in an urban Indonesian context. Using a qualitative descriptive phenomenological design, in-depth, semi-structured interviews were conducted with seven informants aged 18–24 years, consisting of six female and one male participant from diverse family structures, including intact and broken-home backgrounds. Data were analyzed using Giorgi’s descriptive phenomenological method, informed by Family Communication Patterns Theory and Social Learning Theory. The findings indicate that limited open family communication and strong conformity-oriented expectations restrict discussions of sexuality within the family, positioning peer groups as primary sources of relational norms and sexual meaning-making. Peer interactions normalized FWB relationships through shared narratives and social validation, particularly when parental communication about sexuality was constrained. While some informants framed FWB involvement as autonomy-driven and linked to identity exploration, others engaged in such relationships in response to unmet emotional needs, especially within disrupted family contexts. Family-based sexual education was largely prevention-focused, emphasizing pregnancy avoidance while giving limited attention to emotional and relational dimensions of intimacy. The findings demonstrate that involvement in FWB relationships is shaped by interconnected communicative constraints, emotional vulnerabilities, and peer-based social learning processes rather than individual sexual choice alone. This study contributes to broader debates on family-based sexuality education by clarifying how early family communication patterns influence adolescents’ later sexual decision-making and is relevant beyond Indonesia for collectivist and religious societies with similar communicative constraints.